The Interplay Among Children's Negative Family Representations, Visual Processing of Negative Emotions, and Externalizing Symptoms. Issue 2 (25th February 2017) - Davies, Patrick T.; Coe, Jesse L.; Hentges, Rochelle F.; Sturge‐Apple, Melissa L.; van der Kloet, Erika
Abstract : This study examined the transactional interplay among children's negative family representations, visual processing of negative emotions, and externalizing symptoms in a sample of 243 preschool children ( M age  = 4.60 years). Children participated in three annual measurement occasions. Cross‐lagged autoregressive models were conducted with multimethod, multi‐informant data to identify mediational pathways. Consistent with schema‐based top‐down models, negative family representations were associated with attention to negative faces in an eye‐tracking task and their externalizing symptoms. Children's negative representations of family relationships specifically predicted decreases in their attention to negative emotions, which, in turn, was associated with subsequent increases in their externalizing symptoms. Follow‐up analyses indicated that the mediational role of diminished attention to negative emotions was particularly pronounced for angry faces.